Effectiveness of Compassion-Focused Therapy (CFT) and Schema Therapy on Psychological Well-Being and Sense of Psychological Coherence in Infertile Women - Gholami Baker , Nikta; Pourahmadi, Elnaz; Jalali, Mohsen; Mirani, Arastoo (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to compare the effectiveness of compassion-focused therapy (CFT) and schema therapy on psychological well-being and sense of coherence among infertile women. Methods and Materials: A quasi-experimental, pretest-posttest-follow-up design with a control group was used. Thirty infertile women referring to Saarem Hospital in Tehran during the first half of 2024 were randomly assigned to three groups: CFT (n=10), schema therapy (n=10), and waitlist control (n=10). The CFT group received eight sessions, and the schema therapy group received ten sessions. Psychological well-being was assessed using the 18-item Ryff Psychological Well-Being Scale, and sense of coherence was measured with the Flensborg et al. (2006) Sense of Coherence Questionnaire. Data were analyzed using multivariate analysis of covariance (MANCOVA) and Bonferroni post-hoc tests. Findings: MANCOVA results showed significant differences between groups on both psychological well-being and sense of coherence at posttest (Wilks’ Lambda = .350, F(4,54)=18.76, p<.001). Univariate tests indicated significant group effects on psychological well-being (F(2,27)=18.45, p<.001) and sense of coherence (F(2,27)=22.13, p<.001). Post-hoc analyses revealed that CFT significantly improved psychological well-being compared to schema therapy and control at posttest (p<.05), while schema therapy led to greater improvements in sense of coherence compared to CFT and control (p<.05). Both interventions maintained their effects at the one-month follow-up. Conclusion: The findings suggest that compassion-focused therapy is more effective in enhancing psychological well-being, whereas schema therapy is more effective in strengthening sense of coherence among infertile women. Both interventions showed sustained benefits over time, highlighting the importance of incorporating structured psychological treatments into infertility care to promote adaptive functioning and resilience.